Transcranial Direct Current Stimulation (tDCS) over the Left Dorsal Lateral Prefrontal Cortex in Children with Autism Spectrum Disorder (ASD) - Jiujun Qiu; Xuejun Kong; Jihan Li; Jie Yang; Yiting Huang; Minshi Huang; Binbin Sun; Jiayi Su; Helen Chen; Guobin Wan; Jian Kong (Neural Plasticity)
Recently, transcranial direct current stimulation (tDCS) has been applied to relieve symptoms in individuals with autism spectrum disorder (ASD). In this prospective, parallel, single-blinded, randomized study, we investigate the modulation effect of three-week tDCS treatment at the left dorsal lateral prefrontal cortex (DLPFC) in children with ASD. 47 children with ASD were enrolled, and 40 (20 in each group) completed the study. The primary outcomes are Childhood Autism Rating Scale (CARS), Aberrant Behavior Checklist (ABC), and the Repetitive Behavior Scale-Revised (RBS-R). We found that children with ASD can tolerate three-week tDCS treatment with no serious adverse events detected. A within-group comparison showed that real tDCS, but not sham tDCS, can significantly reduce the scores of CARS, Children’s Sleep Habits Questionnaire (CSHQ), and general impressions in CARS (15th item). Real tDCS produced significant score reduction in the CSHQ and in CARS general impressions when compared to the effects of sham tDCS. The pilot study suggests that three-week left DLPFC tDCS is well-tolerated and may hold potential in relieving some symptoms in children with ASD.